CLINICAL OUTCOMES OF IVERMECTIN IN COVID-19 TREATMENT: AN EVIDENCE-BASED CASE REPORT FROM SYSTEMATIC REVIEWS AND META-ANALYSES - Jason Theola; Muhammad Ikrar Hermanadi; Kahlil Gibran; Syarifaha Ihsan (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Ivermectin has demonstrated beneficial results on clinical outcomes in COVID-19 patients. Several countries have included ivermectin in their guidelines, though WHO recommended against its usage. Therefore, this study was aimed to establish the clinical outcomes of ivermectin in COVID-19 patients by an evidence-based method. Method: Article searching was completed in PubMed, Cochrane, and Scopus from July 9 - 10 2021. The results were limited to only systematic reviews and meta-analyses. Hand searching was conducted to obtain relevant studies from external resources. The results were evaluated using inclusion and exclusion criteria. The full texts were obtained and critically reviewed using Oxford Centre for Evidence-Based Medicine critical appraisal tools. Result: Three systematic reviews and meta-analyses were selected and critically reviewed. All three studies were considered valid, important, and applicable. However, the quality of these studies varied from low to high. Conclusion: Overall studies showed that ivermectin has the potential to improve clinical outcomes in COVID-19 patients.